2021
DOI: 10.3389/fonc.2021.659709
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Differentiation Between Malignant Rhabdoid Tumor of the Kidney and Normal Tissue: A Two-Case Report

Abstract: BackgroundMalignant rhabdoid tumor of the kidney (MRTK) is a rare type of tumor that lacks typical clinical manifestations. Herein, we presented clinical data of 2 children with MRTK. In addition, we used a high-throughput RNA-sequencing (RNA-seq), GO analysis, and KEGG signaling pathway analysis to examine gene expression differences at the transcripts level between 2 patients with MRTK and 3 patients with non-tumor diseases without other symptoms.Case reportPreoperative B-scan ultrasonography and computed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In conclusion, married patients showed significant improvement in RR compared with unmarried patients for cancer with a relatively low degree of malignancy, such as patients with ccRCC included in this study. Marriage is not beneficial for highly malignant cancers, such as pancreatic cancer and renal malignant rhabdomyoma tumor ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, married patients showed significant improvement in RR compared with unmarried patients for cancer with a relatively low degree of malignancy, such as patients with ccRCC included in this study. Marriage is not beneficial for highly malignant cancers, such as pancreatic cancer and renal malignant rhabdomyoma tumor ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the German Children's Cancer Registry, the absolute number of reported cases of rhabdoid tumors between 2010 and 2015 was 139, with male prevalence in all cases, in which only 9% of the MRTK were mentioned [ 3 ]. It occurs more frequently in children aged 2-year-old or older and is low in the neonatal form [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tumor has an overall poor prognosis. Recent research found that only one patient out of 35 survived after a five-year follow-up [ 4 ]. The prognosis depends on several parameters, including age, comorbidities, metastases, early detection, and treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have shown that the PI3K-AKT signaling pathway and microRNA-related proteins have a very high potential value for the diagnosis and treatment of MRTK. ( Zhanghuang et al, 2021 ). However, the prognosis prediction of MRTK has not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%